PELATIHAN DAN PENDAMPINGAN APLIKASI SIAPIK PADA PELAKU UMKM DI DESA CIAWIGAJAH - Ririn Nurnovita Sari; Trisa Anggraeni; Nurmeinda Fikihana; Teguh Saputra; Shidik Hamka Ghozali; Tia Latifah; Sri Rokhlinasari (Bajang Institute, 2024)
This training and mentoring aims to equip macaroni MSMEs in Ciawigajah Village to record and apply financial transactions using the Accounting Application System (SIAPIK) and ends with the preparation of financial reports. The method used is in the form of tutorials, discussions, and mentoring practices using a Participatory Action Research (PAR) approach involving macaroni MSMEs in Ciawigajah Village. The results of the training and mentoring show that in recording the finances of macaroni MSMEs in Ciawigajah Village, Beber District, they use the Accounting Application System (SIAPIK) via a device to make it easier to record transactions in the form of inventory purchases, sales of merchandise, and bank loans (installments). Real time information using the Accounting Application System (SIAPIK) helps MSMEs in carrying out operations